IMAJINASI DALAM RUANG POLITIK NASIONAL - Prawoto, Sigit (Studi Budaya Nusantara, 2018)
Abstract The political campaign has so many possibilities to generate an impressive personal image of a politician. The way to communicate a message to the public can be driven directly or using some symbolics peculiarity in a time so that it stimulate some overlying political discourses. The powerful political partis will animate some massif and noisy mass parades in downtown in many different places while the small ones will do it in a calme and small procession and in some cases the do not even organise a single mass parade. The number of people in these carnivals shows the potential power of the partis in the field and in the financial support from the partis and their politicians. In actual tendance the partis politics do the same massif campaign in Medias and social Medias. The mass campaign on facebook and twitter become new approaches in the way to attract the attention of the people even if the campaign in theses socials Medias turn out to be free and wild because the facebook and twitter official's accounts of the partis politics intermingle to those of the publics. The free of the use of those Medias gives a freedom to promote the positive and negative sides of a politician and the so many ways of presentations makes the general election of 2014 hide many controversies that for some years latter on still become a topic of debate in the real and virtual realm.